THE ANALYSIS OF PRE-EXPANSIONS AND PREFERENCE ORGANIZATION OF INVITATION DIALOGUES IN EFL TEXTBOOKS:A CONVERSATION ANALYSIS - Azizah, Fahmia Nur (2015)
This paper, entitled "The Analysis of Pre-Expansions and Preference Organization of Invitation Dialogues in EFL Textbooks: A Conversation Analysis" aims to analyze the presentation of pre-expansions and preference organization of invitation dialogues in textbooks and its accordance with the description of authentic invitation dialogues described in Conversation Analysis (CA) studies. This study was conducted to confirm the research findings showing that most of textbook dialogues are inauthentic and different from real-life conversation. According to CA, one aspect that indicates the dialogue authenticity is sequence organization. In this regard, the researcher examined pre-expansions and preference organization since they are related to the objectives of learning invitation stated in EFL textbooks in Indonesia, which are making, accepting, and rejecting invitation. Qualitative approach and Conversation Analysis method were employed to gather and analyze the data. The findings showed that the five textbooks examined in this study lack presentation of accurate pre-invitation. Some features of preference organization are accurately demonstrated but still contain inadequate interactional function. Moreover, all of the textbooks do not provide any explanation regarding the use of pre-invitation and the features of preference organization. It suggests the necessity of improving the textbook dialogues which closely match the description of authentic conversation sequence in CA studies. --------- Skripsi berjudul "Analisis Pre-Ekspansi dan Organisasi Preferensi pada Dialog Undangan dalam Buku Teks Bahasa Inggris sebagai Bahasa Asing: Sebuah Analisis Percakapan" ini bertujuan untuk menganalisis penyajian pre-ekspansi (pre-expansion) dan organisasi preferensi (preference organization) pada dialog undangan di dalam buku teks dan kesesuaiannya dengan deskripsi dialog undangan autentik yang terdapat pada studi Analisis Percakapan (Conversation Analysis). Penelitian ini dilakukan untuk mengkonfirmasi hasil-hasil penelitian yang menunjukkan bahwa kebanyakan dialog di dalam buku teks tidak autentik dan berbeda dengan percakapan di dalam dunia nyata. Menurut CA, salah satu aspek yang mengindikasikan autentisitas suatu dialog adalah organisasi rangkaian interaksi (sequence organization). Dalam hal ini, peneliti menganalisis pre-ekspansi dan organisasi preferensi percakapan dikarenakan keduanya berkaitan dengan tujuan pembelajaran undangan yang tertera di dalam buku teks Bahasa Inggris di Indonesia, yaitu membuat, menerima, dan menolak undangan. Pendekatan kualitatif dan metode Analisis Percakapan digunakan untuk mengumpulkan dan menganalisis data. Hasil penelitian menunjukkan bahwa kelima buku teks yang diuji dalam penelitian ini kurang menyajikan pre-invitation yang akurat. Beberapa fitur dari organisasi preferensi disajikan dengan akurat namun tetap mengandung fungsi interaksional yang tidak sesuai. Selain itu, kelima buku teks tersebut tidak menyediakan penjelasan apapun mengenai penggunaan pre-invitation dan fitur-fitur organisasi preferensi. Hal ini mengisyaratkan pentingnya mengembangkan dialog di dalam buku teks yang mendekati deskripsi rangkaian interaksi dialog autentik yang terdapat pada studi CA